Analisis Potensi Wilayah Terkait dengan Kondisi Jaringan Jalan dalam Rangka Pengembangan Wilayah Kabupaten Pringsewu - Fransisca Anda Chrisma Dewi (UNIVERSITAS LAMPUNG, 2019)
This research aim to identify and analyze the sectors that are the basis of each district for the development of the Subdistrict. Determining and describing the potential competitive sector of each sub has the greatest potential to contribute to the economic development of Newburn and conditions of the road network that will support the regional development of Fortuna. Of each District in Newburn shows the different basis, mainly due to the Subdistrict area developed into the urban industrial sector emerged as the basis in some districts. The road network is not well with the condition and do not meet the standard of the existing road. With the development of the Subdistrict for Trade and Services are necessary to be an increase in the road, especially the relationship between the center - a center of the preferred road network of collectors.